PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP PENGELOLAAN DIRI SISWA SMP NEGERI 16 KOTA JAMBI - Aifa Nurul Syabina; Rasimin Rasimin; Dinny Rahmayanty (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This study was motivated by the challenges faced by some students in managing their time, emotions, and focus on learning, influenced by peer pressure, home environment, and school assignments. Issues such as procrastination, lack of motivation, and difficulty adhering to rules were observed. Despite these challenges, communication with peers and teachers provided support that helped students cope. However, communication does not always run smoothly due to differing perspectives that may create barriers. The purpose of this research was to examine the influence of interpersonal communication on students' self-regulation at SMP Negeri 16 Kota Jambi, involving a total sample of 173 students. The study utilized a quantitative approach with an ex-post facto research method. The findings revealed that the level of interpersonal communication was categorized as high, with a percentage of 74.96%, while self-regulation was also in the high category, at 73.5%. The coefficient of determination (R Square) was 0.256, indicating that 25.6% of the variance in self-regulation (the dependent variable) could be explained by interpersonal communication (the independent variable), which falls under the